Association between subjective well‐being and presence of primary care dentists in community‐dwelling elderly people: A cross‐sectional study. (30th January 2019) - Mizutani, Shinsuke; Aoki, Hisae; Haresaku, Satoru; Shimada, Kaoru; Ueno, Michio; Kubota, Keiko; Naito, Toru
Abstract : Objective: The aim was to investigate the relationships between subjective well‐being and the existence of primary care dentists in community‐dwelling elderly people. Background: Some studies have reported subjective well‐being focusing on oral health, but no studies have examined the relationship between subjective well‐being and primary care dentists. Methods: This cross‐sectional study used data from community‐dwelling elderly people aged ≥70 years ( n  = 624). The Philadelphia Geriatric Center Morale Scale (PGCMS; range = 0 [low morale]‐17) was used to assess subjective well‐being. Additional information regarding age group, sex, medical consulting situation (ambulatory care/home care), primary care dentists, family structure, economic status, health status was collected via questionnaire. Results: The average PGCMS score in ambulatory care patients (ACP) group who have primary care dentists was highest among community‐dwelling elderly people. In a logistic regression model, a low PGCMS score (0‐11) was independently correlated to 80‐89 age group (OR = 1.70; 95% CI, 1.13‐2.54; P  = 0.008), ≥90 age group (OR = 3.86; 95% CI, 1.83‐8.18; P  < 0.001), unsatisfied for economic status (OR = 2.68; 95% CI, 1.59‐4.53; P  < 0.001), unsatisfied for health status (OR = 3.94; 95% CI, 2.60‐5.98; P  < 0.001) and having no primary care dentists (OR = 1.81; 95% CI, 1.09‐3.01; P  = 0.021) in ACP group. Conclusions: The subjective well‐being of ACP who have primary care dentists was higher than in other people. Primary dentists contributed to the subjective well‐being of elderly people.